FACTORS IMPEDING EXCLUSIVE BREASTFEEDING IN A LOW-INCOME AREA OF THE WESTERN CAPE PROVINCE OF SOUTH AFRICA - Goosen, C.; McLachlan, M.H.; Schubl, C. (Africa Journal of Nursing and Midwifery, 2016)
The promotion of exclusive breastfeeding for the first six months of life is estimated to be the most effective measure to save infants from morbidity and mortality in low-income settings. South Africa is challenged by very poor exclusive breastfeeding practices (6.8-8.3%) during the first six months of life. In the low-income area investigated, the exclusive breastfeeding rate was 6% in 2011. The aim of this study was to describe the factors impeding exclusive breastfeeding practices in a low-income area of the Western Cape Province of South Africa in order to provide recommendations on tailored and generalisable intervention strategies for the promotion of exclusive breastfeeding practices. Focus group discussions were conducted with caregivers and health care workers. Several barriers to exclusive breastfeeding practices were reported and seven themes were identified during data analysis: 1) the perception that infants needed water, gripe water and Lennon's Behoedmiddel; 2) the concern that milk alone does not satisfy an infant; 3) inadequate infant feeding education and support by the health system; 4) the lack of community-based postnatal support; 5) convention and family influence; 6) mothers separated from infants; and 7) local beliefs about maternal behaviour and breastfeeding. The barriers to exclusive breastfeeding practices proved to be multifaceted and interlinked. The influence of convention and community perceptions and beliefs combined with suboptimal infant feeding education by the health system and the lack of local postnatal breastfeeding support initiatives posed an intricate group of barriers to exclusive breastfeeding practices.